The Impact of Corporate Governance on Earnings Quality: Evidence from Chinese Listed Companies - Shao, Xuening (2022)
This paper investigates the effect of corporate governance on earnings quality using Chinese listed companies as an example. Data from 2,862 companies listed on China stock exchanges from 2014 to 2020 are selected as observations to test the impact of corporate governance on earnings quality. This paper mainly studies three indicators of corporate governance: board size, board independence and audit committee size. Earnings quality is determined by discretionary accruals calculated from the modified Jones model as a proxy indicator. In addition, the paper compares the effect of corporate governance on earnings quality before and during the pandemic. The study suggests that board size, board independence and audit committee size all have a significant positive relationship with earnings quality. The impact of audit committee size on earnings quality is found to be weaker during the pandemic.